Re-theorising the pre-adolescent child in School Age Care. Issue 2 (June 2020) - Hurst, Bruce
School Age Care is a setting that is little researched and the research that has been conducted has not often sought the perspectives of older children. This article describes a participatory and ethnographic research project that sought a deeper insight into older children's experiences of an Australian School Age Care setting, seeking their views about how to successfully program for other children their age. Older children in School Age Care are commonly spoken of as rebellious, bored, disruptive and unsuited to School Age Care. The Foucauldian theories underpinning the research challenged the normative developmental discourses that circulate School Age Care. The research shows that older children have access to these developmental and maturational discourses. The participants actively engaged with language, architecture and resources in the School Age Care setting to actively construct themselves as a more mature, distinct category of child. The findings suggest that School Age Care practitioners should be aware of how developmental discourses are both enacted by children and reinforced through programming design and consider the impacts of segregating routines and practices on children's play and leisure. While this research does not 'solve' the question of older children in School Age Care, it unsettles dominant understandings, therefore inviting practitioners to imagine new programming approaches that might improve School Age Care for older children.